Determinan Pengembangan Industri Kecil Dan Menengah Dan Strategi Pengembangannya Di Kabupaten Sarolangun Provinsi Jambi - Suhadi .; Rachmad .; Nurhayani .; Siti Hodijah (JOURNAL OF SHARIA ECONOMICS, 2025)
This study analyzes the determinants of Small and Medium Industries (SMIs) development and formulates development strategies in Sarolangun Regency, Jambi Province, Indonesia. A quantitative descriptive approach was employed, combining multiple linear regression and quantitative SWOT analysis. The independent variables are business capital (X₁), human resource quality (X₂), production technology (X₃), market access (X₄), government support (X₅), and business partnerships (X₆), with SMI development (Y) as the dependent variable. The results show that all six determinants have positive and statistically significant effects on SMI development (p < 0.05), with business capital and government support emerging as the dominant factors. The SWOT mapping positions Sarolangun’s SMIs in Quadrant I (aggressive), indicating an emphasis on leveraging internal strengths to capture external opportunities. Recommended priority strategies include expanding access to finance, strengthening human capital, modernizing production technology, broadening market networks and information, optimizing local policies and services, and reinforcing cross-sector partnerships